Productivity and Profitability of Jackfruit-Eggplant Agroforestry System in the Terrace Ecosystem of Bangladesh - Md. Abiar Rahaman; Atiqur Rahman; Md. Giashuddin Miah; Md. Azizul Hoque; Md. Mezanur Rahman (Turkish Journal of Agriculture: Food Science and Technology)
Multistoried agroforestry systems as a form of jackfruit-eggplant based is increasingly recognized as a promising option to counteract the catastrophic effects of climate change through providing multifaceted benefits. Unfortunately, farmers of Bangladesh did not manage their jackfruit orchard in a scientific manner. Therefore, the present study was aimed to assess the productivity and profitability of jackfruit-eggplant based agroforestry system after modification from a traditional jackfruit orchard during the period of July 2012 to December 2013. Five treatments covering four orientations of jackfruit tree and an open field was used as a control treatment. To observe the growth and economic performance of the system; soil moisture and temperature, DBH, number of fruits per tree, fruit length, fruit width, fruit weight, total yield, BCR, and LER were calculated following different established methods. The yield of jackfruit dramatically increased by 81% in the agroforestry system in compared to sole cropping, while eggplant shows inverse trend. Soil moisture was high in agroforestry system than that of control plot while soil temperature shows reverse pattern. Indeed, agroforestry system had some negative effects on growth performance of understorey crops. Despite, net return and BCR from jackfruit based agroforestry system were 5.58 lakh and 4.56, which was 66 and 45%, respectively higher than sole cropping systems. The LER of jackfruit-eggplant based agroforestry system was 2.17. Considering the main findings, we can elucidate that jackfruit orchards can be transformed to agroforestry system for maximizing production, generating income and conserving environment.